Microdetermination of Palladium(II) using 6-Chloro-3-hydroxy-7-methyl-2-(2′-thienyl)-4-oxo-4H-1-benzopyran - Kaur, N.; Agnihotri, N.; Berar, U. (Asian Journal of Chemistry, 2020)
A simple, rapid, sensitive and selective extractive spectrophotometric method is developed for the trace determination of palladium(II) from NaHCO3 medium using 6-chloro-3-hydroxy-7-methyl-2-(2′-thienyl)-4-oxo-4H-1-benzopyran (CHMTB) as a colouring agent. The proposed metal complex can be quantitatively extracted into ethyl acetate and absorbs maximum in the wavelength range 415-426 nm. The 1:1 yellow complex obeys linearity over the Pd(II) concentration range of 0-2.6 μg mL-1; the correlation coefficient being 0.9998. The molar annihilation coefficient and Sandell′s sensitivity when applying spectrophotometric determination at 420 nm, were 6.173 × 104 L mol-1 cm-1 and 0.0017 μg Pd(II) cm-2, respectively. The proposed method is free from the interference of Os(VIII), Cr(VI), Mo(VI), V(V), Nb(V), Ce(IV), Se(IV), Zr(IV), Pt(IV), Ru(III), Ir(III) and Fe(III) . The method was effectively applied to the determination of Pd(II) in various samples including palladium charcoal catalyst and water.